Case Report: Diagnosis and Assessment of Cure Approaches for Acute Schistosomiasis in Pre-School Children - Cavalcanti, Marta G.; Engel, Délia Celser; de Araujo Cunha, Aline Fernandes; Peralta, José Mauro (Frontiers in Immunology, 2021)
Acute schistosomiasis (AS) manifests with a broad spectrum of clinical features in pediatric populations. Diagnosis may be difficult in the absence of detectable numbers of eggs. As a result, new approaches may be required to achieve an accurate diagnosis. Optimal praziquantel (PZQ) treatment regimen for young children is debatable. Also, the post-treatment response is still poorly evaluated due to the lack of reliable markers. A group of 6 children (a toddler and 5 pre-school children) and one pre-adolescent were investigated for AS clinical manifestations and followed-up for two years after treatment. Ova detection was performed by Kato-Katz (KK) and presence of Schistosoma mansoni DNA was assessed by real-time PCR (rt-PCR) in stool samples. IgG and IgE anti-Schistosoma levels and urinary antigen were detected by ELISA and point-of-care circulating cathodic antigen (POC-CCA) testing in serum and urine, respectively. AS clinical symptoms were present in 5/7 (71.4%) of the infected children, and hypereosinophilia was detected in all of them. Ova detection and serology were positive in only 3/7 (44.9%) and 4/7 (57.1%), respectively. However, real-time PCR (rt-PCR) showed the presence of Schistosoma DNA in 6/7 (85.7%) of the cases, and urinary antigen was detected in all infected children. The long-term follow-up after treatment with three doses of PZQ (80mg/kg/dose), showed high cure rates (CR) as demonstrated by the DNA-based assay as well as reduced levels of side effects. CR based on urinary antigen detection ranged from 28.6 to 100%, being the highest CR due to double testing the 2-year post-treatment samples. The results suggest that high dose and repeated treatment with PZQ might be effective for AS in young children. Also, new laboratory markers should be considered to diagnosis and monitor the drug response.